2001
DOI: 10.1016/s0022-2275(20)31499-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of apoA-II in lipid metabolism and atherosclerosis: advances in the study of an enigmatic protein

Abstract: Our understanding of apolipoprotein A-II (apoA-II) physiology is much more limited than that of apoA-I. However, important and rather surprising advances have been produced, mainly through analysis of genetically modified mice. These results reveal a positive association of apoA-II with FFA and VLDL triglyceride plasma concentrations; however, whether this is due to increased VLDL synthesis or to decreased VLDL catabolism remains a matter of controversy. As apoA-II-deficient mice present a phenotype of insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(25 citation statements)
references
References 111 publications
1
24
0
Order By: Relevance
“…Non-denaturing PAGE analysis indicated that the presence of apoAII might also have an advantage in the formation of compact lipoprotein particles, such as HDL. Based on previous evidence that apoAII exists predominantly in HDL (Blanco-Vaca et al, 2001) and the apoE-AII complex prefers HDL to low-density lipoproteins (Weisgraber, 1990), the present finding is certainly reasonable. Our finding that the particle sizes of apoE2-Lp were smaller than those of apoE3-Lp led us to the idea that Cys158 or the apoAII-E2-AII complex may be involved in the formation of apoE-containing lipoprotein particles.…”
Section: Discussionsupporting
confidence: 83%
“…Non-denaturing PAGE analysis indicated that the presence of apoAII might also have an advantage in the formation of compact lipoprotein particles, such as HDL. Based on previous evidence that apoAII exists predominantly in HDL (Blanco-Vaca et al, 2001) and the apoE-AII complex prefers HDL to low-density lipoproteins (Weisgraber, 1990), the present finding is certainly reasonable. Our finding that the particle sizes of apoE2-Lp were smaller than those of apoE3-Lp led us to the idea that Cys158 or the apoAII-E2-AII complex may be involved in the formation of apoE-containing lipoprotein particles.…”
Section: Discussionsupporting
confidence: 83%
“…Several apolipoprotein types exist with diverse physiological functions and corresponding roles in different diseases (Table 1). Tangier disease, amyloidosis [44,70], cardiovascular disease progression [70,71], Alzheimer disease [72,73], sepsis [74], schizophrenia [75], chronic pain [76] A2 HDL Lipid transport, inflammation, neuronal regeneration [69] Cardiovascular disease progression [43], amyloidosis [44,77] A4 Chylomicrons, VLDL-C, HDL, hypothalamus…”
Section: Cholesterol and Lipoproteins-function And Propertiesmentioning
confidence: 99%
“…Conversely, the lipid profile may be a pivotal component of the several co-morbidities typically seen in sepsis survivors. Though direct links between lipid profile abnormalities and post-septic conditions are not studied in-depth, cholesterol metabolism is critical in the natural history of dementia, cognitive decline, and cardiovascular system performance [ 43 , 44 , 45 ]. All of these conditions are often seen in the aftermath of sepsis [ 10 , 29 , 30 , 32 , 33 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, our study demonstrated that apo AI level significantly exceeds accepted norms, both at the time of diagnosis and after 12 months of the study. On the other hand, apo AII level (despite the significant increase in concentration) is significantly below accepted norms at the same time points [ 21 , 22 ]. The above results suggest a protective mechanism against metabolic disturbance which occurs at the onset of T1DM.…”
Section: Discussionmentioning
confidence: 99%